(untitled) (Medico Legal Update, 2020)
Normatively, the follow up on the Constitutional Court’s Decree has been regulated in the Constitution No.12 of 2011. Yet, the mentioned norm has not optimally regulated the follow up of the Constitutional Court’s Decree as one of the main sources in the planning and the renewal of the national law. This is shown by the fact that there was a norm which was annulled by the Constitutional Court, yet it was still written in the new Constitution. Because of that, the Constitutional Court’s verdict, especially those regarding the politics of judicial law, is crucial to be included in the national law planning and development documents as a guide for the lawmakers in the form of the Constitution. This is because the Constitutional Court’s decree includes the politics of the judicial law, which determines the road of the national health law’s development, so that the constitution in the aspect of health will not be against the 1945 Constitution. This research is a qualitative study, by using the post-positivism paradigm and the juridical-normative approach. The research approach used is statute approach and case approach. The research approach is used to see the politics of the judicial law contained in the Constitutional Court’s Decree which should have been the guide of the national health law development.